Synergistic antibacterial effects of closantel and its enantiomers in combination with colistin against multidrug resistant gram-negative bacteria - Ding, Tongyan; Guo, Zeyu; Fang, Liangxing; Guo, Wenying; Yang, Yuxi; Li, Yafei; Li, Xiarong; He, Limin (Frontiers in Microbiology, 2024)
Drug combinations and repurposing have recently provided promising alternatives to cope with the increasingly severe issue of antibiotic resistance and depletion of natural drug molecular repertoires that undermine traditional antibacterial strategies. Closantel, an effective adjuvant, reverses antibiotic resistance in gram-negative bacteria. Herein, the combined antibacterial enantioselectivity of closantel is presented through separate enantiomer studies. Despite yielding unexpected differences, two closantel enantiomers (R, S) increased colistin activity against gram-negative bacteria both in vitro and in vivo. The fractional inhibitory concentration indices of R-closantel and S-closantel combined with colistin against Pseudomonas aeruginosa, Klebsiella pneumoniae, and Escherichia coli ranged from 0.0087 to 0.5004 and from 0.0117 to 0.5312, respectively. This difference was further demonstrated using growth inhibition assays and time-killing curves. Mechanistically, a higher intracellular concentration of R-CLO is more effective in enhancing the antimicrobial activity of combination. A mouse cutaneous infection model confirmed the synergistic stereoselectivity of closantel. This discovery provides novel insights for developing precision medication and containment of increasing antibiotic resistance.